Neutralizing activities of human immunoglobulin derived from donors in Japan against mosquito-borne flaviviruses, Japanese encephalitis virus, West Nile virus, and dengue virus - Yunoki, Mikihiro (Biologics, 2016)
Japanese encephalitis virus (JEV), West Nile virus (WNV), and dengue virus (DenV) are causal agents of Japanese encephalitis, West Nile fever, and dengue fever, respectively. JEV is considered to be indigenized and widespread in Japan, whereas WNV and DenV are not indigenized in Japan. Globulin products seem to reflect the status of the donor population according to antivirus neutralization activity. However, the anti-JEV, -WNV, and -DenV neutralization activities of globulin products derived from donors in Japan have not been clarified. Furthermore, potential candidates for the development of an effective immunotherapeutic drug for encephalitis caused by JEV, WNV, or DenV have also not been identified. Therefore, the aim of this study was to determine the overall status of the donor population in Japan based on globulin products by evaluating anti-JEV, -WNV, and -DenV neutralizing activities of intravenous immunoglobulin. Overall, intravenous immunoglobulin products showed stable neutralizing activity against JEV but showed no or only weak activity against WNV or DenV. These results suggest that the epidemiological level against WNV and DenV in the donor population of Japan is still low, suggesting that these viruses are not yet indigenized. In addition, JEV vaccinations and/or infections in the donor population do not induce a cross-reactive antibody against WNV.